DIGITAL MARKETING AS A MARKETING SOLUTION FOR RUMAH JAMU MIRASA, SAWANGAN VILLAGE, LEKSONO, WONOSOBO - Maulana Akbar, Muhamad Asif; Kaukab, M. Elfan; Efendi, Bahtiar; Jannati, Nur Baiti; Azka, Muhammad Gilang Maulana (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia’s economy, particularly as major contributors to employment and the Gross Domestic Product (GDP). One of the promising MSMEs is Rumah Jamu Mirasa in Sawangan Village, Wonosobo Regency. However, this business faces challenges in its conventional marketing methods, which result in relatively low income. This community service program aims to enhance the competitiveness of Rumah Jamu Mirasa through the implementation of digital marketing. The method used is Participatory Action Research (PAR), involving MSME actors actively in problem identification, planning, implementation, and evaluation. The results show an increase in MSME actors’ understanding of digital marketing strategies and a rise in sales turnover after utilizing social media and e-commerce. These findings demonstrate that digitalization has a positive impact on MSME development, particularly in expanding market access and increasing sales. This program is expected to serve as a model for empowering local MSMEs to compete in the digital era.